Pengembangan Potensi Pantai Echo Beach Sebagai Daya Tarik Wisata Di Desa Canggu Kecamatan Kuta Utara - Hanum, I Putu Aditya Adi Guna; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2018)
Pantai Batu mejan (Echo Beach). Beach Echo Beach is located in the village of Canggu, northern district of Kuta, Badung regency. Distance traveled to this location approximately 14 km from the city of Denpasar. Many foreign tourists come this beach for sunbathing, swimming and surfing while enjoying the beautiful scenery at sunset (sunset). The beach is famous as a sport surf for foreign tourists. The purpose of this study to determine the potential of Echo Beach and to determine the development strategy in Echo Beach.                        The method of research is qualitative descriptive analysis with SWOT approach. The technique of collecting data is divided into four: observation, in-depth  interview, documentation and literatureFor informants using purposive sampling technique. Results from this study is the tourism potential held in Turkish Echo Beach as a tourist attraction is the natural potential as sport surfing. Cultural potential that there is a sacred place (temple) and the Rejang Dance and Mask Dance. In anticipation of threats and weaknesses and increase the opportunity and power to develop the potential of Echo Beach Beach this to be sustainable, then reviewing the SWOT approach for Coastal Development Strategy in Echo Beach.   Key words: Strategy Development , Potential Tourism , Coastal Tourism